How do you solve (x - 2) ^ { 2} + 3= 4?

2 Answers
Apr 28, 2018

x=3 and x=1

Explanation:

first expand the quadratic equation
x^2-4x+4+3=4
then sum all the unknown and the constant which will give you
x^2-4x+3=0
then factorise the equation and u get
(x-3)(x-1)=0
therefore x=3 and x=1

Apr 28, 2018

x=1" or "x=3

Explanation:

"isolate "(x-2)^2" by subtracting 3 from both sides"

rArr(x-2)^2=4-3=1

color(blue)"take the square root of both sides"

sqrt((x-2)^2)=+-sqrt1larrcolor(blue)"note plus or minus"

rArrx-2=+-1

"add 2 to both sides"

rArrx=2+-1

rArrx=2-1" or "x=2+1

rArrx=1" or "x=3